2019
DOI: 10.1111/jgh.14666
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of gene‐edited pigs expressing human blood‐coagulation factor VII and albumin for bioartificial liver use

Abstract: Background and Aim Bioartificial livers (BALs) are considered as a solution to bridge patients with acute liver failure to liver transplantation or to assist in spontaneous recovery for patients with end‐stage liver disease. Pig is the best donor of hepatocytes for BALs in clinical trials, because metabolic and detoxification function of its liver are close to human. However, using pig hepatocytes for BALs remains controversial for safety concern owing to nonhuman proteins secretion. Herein, we attempt to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This result indicates HR remains a low-efficiency event in primary fibroblast, even with the aid of CRISPR. Previous reports showed that CRISPR-mediated HR occurred in an efficiency range from 0 to 41.2% in pig fetal fibroblast with a very low rate in most cases, far less than the CRISPR-mediated knockout efficiency [ 14 , 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates HR remains a low-efficiency event in primary fibroblast, even with the aid of CRISPR. Previous reports showed that CRISPR-mediated HR occurred in an efficiency range from 0 to 41.2% in pig fetal fibroblast with a very low rate in most cases, far less than the CRISPR-mediated knockout efficiency [ 14 , 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…to reduce complement activity in xenotransplantation [ 41 ]. Although most knock-in pigs have been generated by SCNT using gene-edited somatic cells carrying transgenes as donor cells [ 31 , 43 , 44 , 104 , 105 , 106 , 107 , 108 , 109 ], cytoplasmic microinjection of gene editors can also be used to successfully generate knock-in pigs [ 49 , 110 ]. However, knock-in pigs have not been successfully generated by electroporation-mediated methods, because the introduction of large transgenes for knock-in is difficult using electroporation alone in pigs, as described above.…”
Section: Current Status and Future Prospects Of Gene-edited Pigsmentioning
confidence: 99%
“…Targeted changes in the animal genome are likely to initiate a new era of bio-pharming [ 195 ]. Healthcare applications include production of target-specific stem cells and therapeutic proteins [ 196 ], mAbs [ 190 ], released into the milk of animals, to the use of genetically modified (GM) animals to produce organs for xenotransplantation are envisaged.…”
Section: Scnt Vis-à-vis Bio-pharmingmentioning
confidence: 99%